Mejoramiento del nivel de voltaje en los alimentadores primarios Paquisha y Los Encuentros de la EERSSA mediante la ubicación óptima de reguladores - González Hidalgo, Silvia Mercedes (2024)
This thesis focuses on the improvement of voltage levels in the primary feeders Paquisha and Los Encuentros of EERSSA through the optimal placement of voltage regulators. The main objective of the study is to reduce voltage drops and ensure compliance with the standards established in regulation ARCERNNR 002/20 for medium voltage levels, thereby improving the quality of electrical service in the areas supplied by these feeders. To achieve this objective, simulations were conducted using Cymdist software, which, based on load distribution derived from current maximum demand and projected over 10 years, allowed for the identification of critical points with significant voltage drops. This software provided a detailed analysis of EERSSA's electrical networks, facilitating the assessment and diagnosis of the feeders. The results indicated that the Los Encuentros feeder met the requirements of ARCERNNR 002/20 in 60% of its total length, with voltage drops between 6% and 10%. On the other hand, the Paquisha feeder showed compliance in only 10% of its length, with voltage drops exceeding 20% in some areas. Following the implementation of voltage regulators and other technical solutions, voltage drops were reduced to levels permitted by the regulation, all remaining below 6%, even considering demand projections for 5 and 10 years. Finally, it is concluded that the installation of voltage regulators, along with additional improvements such as network repowering and phase load balancing, was effective in meeting regulatory requirements, significantly reducing voltage drop percentages and ensuring a quality electrical service in accordance with the current regulation. Keywords Voltage improvement, voltage regulators, voltage drops, service quality, Cymdist, network upgrades, primary feeders.